To find the solution to the system of equations given by \( y = 2x - 1 \) and \( y - 3 = 4x \), we can solve them simultaneously.
First, let's rewrite the second equation in slope-intercept form:
- Start with the equation: \[ y - 3 = 4x \] 2. Add 3 to both sides: \[ y = 4x + 3 \]
Now we have two equations to work with:
- \( y = 2x - 1 \)
- \( y = 4x + 3 \)
Since both equations equal \( y \), we can set them equal to each other:
\[ 2x - 1 = 4x + 3 \]
Next, let's solve for \( x \):
- Subtract \( 2x \) from both sides: \[ -1 = 2x + 3 \]
- Subtract 3 from both sides: \[ -4 = 2x \]
- Divide by 2: \[ x = -2 \]
Now that we have \( x \), we can substitute it back into one of the original equations to find \( y \). Let's use \( y = 2x - 1 \):
\[ y = 2(-2) - 1 \]
Calculating that:
\[ y = -4 - 1 = -5 \]
Thus, the solution to the system of equations is:
\((x, y) = (-2, -5)\)
So, the ordered pair is:
\[ \boxed{(-2, -5)} \]